Erythema Multiforme Major after Whole Brain Radiotherapy: A Case of Emar Syndrome?. (May 2013) - Bottoni, U.; Nisticò, S.; Amoruso, G.F.; Sacco, A.; Arcidiacono, V.; Calvieri, S.
We report the case of a woman with a 4-year history of metastatic breast carcinoma presenting a large erosive area on her scalp plus erosive lesions on the lips and in the mouth and erythematous plaques with vesicles on the trunk and upper limbs. In this case, contrary to other reports, the most important trigger for this syndrome was radiotherapy rather than the systemic medications administered. Therefore we propose the term EMAR (erythema multiforme associated to radiotherapy) to describe this case.